2002
DOI: 10.1136/jcp.55.5.393
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of intraepithelial lymphocytes in human duodenum: what is normal?

Abstract: These results suggest that 25 IELs/100 epithelial cells (mean +2 SD) should be taken as the upper limit of the normal range for duodenal mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(59 citation statements)
references
References 7 publications
2
53
2
1
Order By: Relevance
“…They found significantly higher intraepithelial lymphocyte counts in biopsies from areas of duodenal ulceration and severe nonspecific duodenitis, compared to controls. Hayat et al 30 found raised intraepithelial lymphocyte counts, in the second part of the duodenum, in 4/13 (31%) patients with H. pylori-associated lymphocytic gastritis. Gastric intraepithelial lymphocyte counts decreased after treatment of H. pylori infection but the duodenal intraepithelial lymphocytosis persisted.…”
Section: Discussionmentioning
confidence: 97%
“…They found significantly higher intraepithelial lymphocyte counts in biopsies from areas of duodenal ulceration and severe nonspecific duodenitis, compared to controls. Hayat et al 30 found raised intraepithelial lymphocyte counts, in the second part of the duodenum, in 4/13 (31%) patients with H. pylori-associated lymphocytic gastritis. Gastric intraepithelial lymphocyte counts decreased after treatment of H. pylori infection but the duodenal intraepithelial lymphocytosis persisted.…”
Section: Discussionmentioning
confidence: 97%
“…11 More recently, however, small adult studies have considered the upper limit of normal for duodenal IELs as 20-25 IELs/100 epithelial cells, depending on the method of counting. 12,13 Later, Corazza and Villanacci adopted an upper limit of 25 IELs in their new histological classification for coeliac lesions. 25 The guidelines of the European Society for Paediatric Gastroenterology, Hepatology and Nutrition for the diagnosis of CD also stated a limit of 25 IELs/100 enterocytes to define the infiltrative lesion of CD, 4 while the North American Society for Paediatric gastroenterology, Hepatology and Nutrition opted for 30 IELs in their guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, mild intraepithelial lymphocytosis has also been described in healthy individuals with varying prevalence in different studies. [11][12][13] Because the presence and titres of coeliac-associated antibodies are known to correlate with the extent of pathological damage, 14 finding…”
Section: Discussionmentioning
confidence: 99%
“…Thickness of the section is important as well, and it has been suggested that accurate evaluation requires well-oriented 3-to 4-m sections. 6,7 The upper limit of IELs in the normal proximal small bowel previously was considered to be 40/100 epithelial cells. However, this figure was based on counts performed on jejunal capsule biopsies, where IEL counts inherently are higher than in the duodenum.…”
Section: Normal Villus Architecture and Intraepithelial Lymphocyte Countmentioning
confidence: 99%
“…8 In more recent studies utilizing thincut sections and endoscopically obtained biopsies, several authors have shown the upper limit of normal for the duodenum to be 20-25 IELs/100 epithelial cells. 6,7 It also has been emphasized that a greater density of IELs is seen in the crypts and, normally, a decrease in number from the base toward the tip is noted. 9 Consequently, counting IELs at the tips of the villi and observing a lack of decrescendo from crypts to tips have been recommended as the most useful method of confirming an increase (Figure 1).…”
Section: Normal Villus Architecture and Intraepithelial Lymphocyte Countmentioning
confidence: 99%